Utilizing narratives to promote gender equality in the classroom - Meicky Shoreamanis Panggabean; Rika Kristyanti Praba Gracia (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Sexism is an ongoing issue which happens in many layers of the society, including educational institution such as school. Students witness and experience sexism in daily life may it be inside or outside the school and it may affect them negatively. Students should be guided and facilitated to be aware of sexism as well as to understand gender equality between men and women and its importance. This paper uses descriptive qualitative method to dig deeper about the existence of sexism at school and narrative as a tool to promote gender equality to students. The result shows that there are various forms of sexism that may happen in school and students should be guided to be aware of those sexism forms. Narrative can be an effective tool to promote gender equality to students because it is easier to comprehend, fun, engaging, relatable, and is able to shape people??